Uterine rupture - incidence and determinants in a teaching institute - Archana Kori; Sonu Kumar Batham (Barpeta Obstetrics and Gynaecological Society, 2022)
Background: Maternal mortality is a major public health issue in India and Indian government run various programs to improve the scenario in present. Uterine rupture is an obstetrical emergency which may lead to serious undesired complications to mother and neonate and may lead to their mortality. Indian women come from various strata of society, economic background; even most of the population is not aware about these programs run by government for their wellbeing and even basic health rites and facilities provided to them. Objectives: In this study we assessed the incidence of ruptured uterus and the factors associated with, in remote Indian population at a tertiary level health facility. Methods: Prospective observational study conducted at UMAID Hospital between 1'st January 2012 to 31'st December 2013. The data related to cases of ruptured uterus and interventions taken to manage were collected and incidence and factors associated were analyzed and tabulated. Results - A total of 44464 deliveries were conducted in the period of two years, out of them 104 were the cases of ruptured uterus that gives the incidence of 1 in 427 deliveries. Previous uterine scar was found the most common risk factor (56.7%) followed by obstructed labour (20.19%) and multiparity (18.26%). Uterine tear repair was done in 63.5% cases and hysterectomy was done in 35.6 % cases, one patient died without any intervention could be performed. Conclusion: Incidence of ruptured uterus and its complications were high in the study population and the possibility of many more unreported cases can't be denied due to lack of awareness and lack of facilities. It reflects the need for improvement in maternity services and strong collaboration of information with referring health facilities to ensure prompt referral and management.